1994
DOI: 10.1021/j100101a013
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Syn-Anti Preference for Carboxylic Acids along the Reaction Coordinate for Proton Transfer. Implications for Intramolecular Catalysis

Abstract: Carboxylate anions are more basic on the syn side because carboxylic acids are more stable with the proton syn to the carbonyl oxygen than anti. This led Gandour to propose that carboxylic anions should act as catalytic bases, as in enzymes, better on the syn side than the anti. However, numerous experimental tests have failed to reveal a strong preference. We resolve this problem by showing, on the basis of Linnett structures and MO calculations, that as a proton gradually departs from its firm syn position i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…Experimental and theoretical studies in the gas phase and solution confirm that the syn lone pairs in carboxylates are more basic, although the difference in basicity of the two carboxylate lone pairs is not as large as originally proposed. , …”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Experimental and theoretical studies in the gas phase and solution confirm that the syn lone pairs in carboxylates are more basic, although the difference in basicity of the two carboxylate lone pairs is not as large as originally proposed. , …”
Section: Introductionmentioning
confidence: 67%
“…Experimental and theoretical studies in gas phase and solution confirm that the syn lone pairs in carboxylates are more basic, although the difference in basicity of the two carboxylate lone pairs is not as large as originally proposed. 6,7 The carboxylate group, like other hydrogen-bonding acceptors, can play a role for directing molecular organisation of catalytic components along with promoting catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review article discusses the competition between intramolecular and intermolecular hydrogen bonds in solution, stating that an intramolecular hydrogen bond may be disrupted in protic solution, such as water, when the increase in internal energy is offset by two or more solute–solvent intermolecular hydrogen bonds. Another study found that the carboxyl group has no strong preference, kinetically and thermodynamically, for the syn (or anti ) conformation in proton transfer catalysis . The anti state may also be important to consider when calculating solvation free energies .…”
Section: Introductionmentioning
confidence: 97%
“…Another study found that the carboxyl group has no strong preference, kinetically and thermodynamically, for the syn (or anti ) conformation in proton trans-fer catalysis. 13 The anti state may also be important to consider when calculating solvation free energies. 14 Finally, the anti conformation is not insignificantly represented in structures from the Cambridge Structural Database, 15 supported by related crystallographic and theoretical charge density studies.…”
Section: Introductionmentioning
confidence: 99%